'A large population, famous for their military qualities': Londoners at war, c. 1000–1200. (November 2022) - Gerrard, Daniel
Abstract: The scholarship of high medieval warfare tends not to emphasize the contribution made by urban communities, regarding cities as the passive objects of military campaigning. This article shows that the inhabitants of medieval London, however, had emerged as an organized military community from an early date, and were regarded by contemporaries as unusually disciplined, effective, fighters.